AN EXPLORATORY STUDY ON THE CARBON CREDIT AS AN INVESTMENT - Silva, Luciano Ferreira da; Macedo, Amanda Helena de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706315 This study was constructed to enable a greater understanding about the Carbon Credit Market,and the research method to realize it was the deductive qualitative approach, being used for itspreparation bibliographic and documentary, and structured interview with people working in thissector. It was possible to verify the operation in the generation and trading of Carbon Credits.Since the main existing environmental management tool for this market is the Kyoto Protocol, andits main instrument is the Clean Development Mechanism (CDM). Based on this structureappeared the carbon credits that encourage the reduction of GEEs allowing bilateral negotiations.Thus, there was the creation of trading on the stock exchanges and the cap and trade system, andthese negotiations can become profitable. However, there is still uncertainty about its future, asthis structure is based on mechanisms valid until 2012.